Experimental Performance Analysis of Refrigerant Mixture of R22/R152a in Air Conditioning System - Kaushik, Rajneesh (International Journal For Research In Mechanical & Civil Engineering, 2015)
In Indian households air conditioning system uses R22 refrigerant which has a very high Global Warming Potential (GWP) of 1700 and a ozone depletion potential (ODP) of 0.05.Hence a new refrigerant of low GDP is found. R152a is recognized as an option to R12 and R22 refrigerants. In this paper an experimental analysis has been done to lessen the usage of R22 with the Hydrocarbon Refrigerant mixtures (HCM) of R22 and R152a refrigerants in the proportion of 30:70, 50:50, and 70:30 by mass. Experiments were carried out by continuous running tests under an ambient temperature of 32°C. The performance of the system predicted that the HCM could be a long term replacement for R22 (chlorodifluoromethane).